A Critical Discourse Analysis of A Political Talk Show on The 2019 Indonesian Presidential Election - Muhassin, Mohammad (English Education: Jurnal Tadris Bahasa Inggris, 2021)
Political discourse on the 2019 Indonesian presidential election has been studied from a variety of linguistic viewpoints.  However, the  pros and cons discourse on  Joko Widodo's coalition with Prabowo in spite of their rivalry has not been examined through  critical discourse analysis.  This study aims to explore the text structure, social cognition, and social context of the pros dan cons discourse as the theme of Mata Najwa talk show. This is a kind of qualitative analytical research using van Dijk’s (1996, 2015) critical discourse analysis framework. The data comprised utterances of the talk show participants examined through three levels of analysis: description of text structure, interpretation of social cognition, and explanation of social context. The study found the use of macrostructure, superstructure, and microstructure as textual elements that support the discourse theme. Meanwhile, the theme selection is influenced by the host’s ideology that serves the theme's pro-coalition stance. The social context underlying the discourse production is the representation of  Joko Widodo, who utilized his power to forge a coalition with the opponents through political bargaining. The implication of this study is to increase public awareness on the importance of critically viewing political news so that the negative excesses of political propaganda do not easily provoke them through mass media.